Mutations in Human Genetic Disease - Cooper, David N.; Chen, Jian-Min (IntechOpen, 2012)
Different types of mutation can vary in size, from structural variants to single base-pair substitutions, but what they all have in common is that their nature, size and location are often determined either by specific characteristics of the local DNA sequence environment or by higher order features of the genomic architecture. The genomes of higher organisms are now known to contain "pervasive architectural flaws" in that certain DNA sequences are inherently mutation prone by virtue of their base composition, sequence repetitivity and/or epigenetic modification. In this volume, a number of different authors from diverse backgrounds describe how the nature, location and frequency of different types of mutation causing inherited disease are shaped in large part, and often in remarkably predictable ways, by the local DNA sequence environment.